Placebo Effect: : A Surprising Link Between Mind and Body - Touny, Lena; Vento, Christopher "Gabby"; Pabon, Daniella Gamboa (Translation: The University of Toledo Journal of Medical Sciences, 2025)
The graph to the right describes a study of 80 patients with irritable bowel syndrome (IBS). Patients either got no treatment or were given a placebo pill. When given the pill they were told “Placebo pills are made of an inert substance, like sugar pills, and have been shown in clinical studies to produce significant improvement in IBS symptoms through mind-body selfhealing processes.” The graph clearly shows that patients getting the pill did better than those without. How is this possible? In the space below, 1) speculate how the mind-body connection could lead to such an improvement in symptoms, and 2) discuss how this process might be at play in the pharmacological treatment of brain diseases?